DESAIN DATABASE UNTUK OPTIMALISASI SISTEM PREDIKSI TRANSAKSI PENJUALAN - Sucipto, Sucipto; Indriati, Rini; Hariawaan, Fitra Bagoes (STKIP PGRI Tulungagung, 2017)
The advance of informational technology is expected to be a tool which helps data tabulating process.Â Management and usage of the data systematically can produce detailed information. The important of data management is able to enhance the quality of information that is processed. Data management is started from the storage system of data namely database design. In the database design, the thing that should be heeded is the relation of each table inside of it. The relation among the table shows the linkages data that will be processed to be essential information. In this research, the focused discussion is optimalizing a table for further tabulating towards a marketing informational system database.Â The database that will be optimalized will be used to marketing prediction tabulation. In tabulating stage, data prediction in database will be exported into two databases namely PostgreSQL and MariaDB. The data used for examining amount 476619 marketing data is taken from marketing transaction among 2015-2017. This research data is tabulated using join table that produce 374 data. The data is the information that will be used for marketing prediction. Based on rapidity examination of marketing data tabulation by using PostSQL indicates slight difference around 0.26 seconds faster than MariaDB. The research result of database optimalizing design which has been made shows that PostgreSQL is better in data tabulating rapidity than MariaDB